(3eNJGQGJ GdfhGRd aj GdMhGOKs - (3Ydj Hf CHj HcQ Hf YHO GdLdjd GdaQZGfj GdeQZjfGfj, HQgGf GdOjf CHh GdMSf,J (B593 (3g` s ((3eMeO Hf eMeO Hf NVQ GdUGdMi GdMfai s)
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf cJGH GdWgGQGJ , GdWgGQI ai GddZI (B: (3YHGQI Yf GdfXGaI s
(3BNQgG (B:s
(3hcPG GHQjeG aNGW Hg Tb HWfg jaJb YfOg , hYfOfG dG jaJb hGddg CYde HGdUhGH s
(3GdfSNI HgG MhGTs
(3HChdg agQSs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B266 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B45s
Keywords: (3Gdabg GdMfajs